If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 3x = 5fory Reorder the terms: 3x + 4y = 5fory Solving 3x + 4y = 5fory Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 3x + 4y + -4y = 5fory + -4y Combine like terms: 4y + -4y = 0 3x + 0 = 5fory + -4y 3x = 5fory + -4y Divide each side by '3'. x = 1.666666667fory + -1.333333333y Simplifying x = 1.666666667fory + -1.333333333y
| 4-12y+9y^2=0 | | s-1=22 | | -1=10z-4 | | 1cx+qy=t | | k^2-11k+28=0 | | 81-18x+x^2=0 | | 85-3x=24x+22 | | 12+1/3a=2 | | -4(-2)(-1)(6)= | | 4x+12=9x-12 | | 3(2x-1)+3=4x | | X^2-5+1=0 | | -x+6=26 | | 6w(m-5)=108 | | 6y-5=25 | | 5(8a-b)-7(8b-6a)= | | 5(6+w)=4(2+w) | | 7+13z=6z | | 4y^2-7y=2 | | -5(6n+2)=7n-7 | | 4(-p+1)=3(-4+6p)-2p | | 0.12d+0.3e=2.76 | | 2b-c=13 | | 2x-4(7x-12)=178 | | 4/9r=8 | | -5x-3x=11-7x | | -7x+4(6x-17)=-153 | | 1/3y-5/6=-2/3y-2/3 | | 3x+5y=35slope | | 4x-3(4x-3)=49 | | 0.6d+0.05e=-4.5 | | 11a+5= |